Meta-Analysis of the Impact of Data Theft on Customer Trust Levels in Banking Services - Risky Mezi Muria; Imam Wahyudi; Ika Oktaviana Dewi (Institut Agama Islam Al-Fatimah Bojonegoro, 2025)
This study aims to analyze the impact of data theft on the level of customer trust in banking services through a meta-analysis approach. Data theft has become a significant threat to the banking industry, which not only causes financial losses but also affects customer trust in banking institutions. By collecting and analyzing data from various previous studies, this study explores the factors that influence customer security perceptions, perceived risks, and levels of trust after a data theft incident. The results of the meta-analysis indicate that data theft significantly decreases customer trust levels, which in turn affects their decision to use online banking services. The findings also identify that implementing strong security measures and transparency in incident handling can help restore customer trust. This study provides important insights for banks and regulators in developing strategies to improve data security and rebuild customer trust in the digital era